Approach for Determination of Maximum Reclaimed Asphalt Pavement Content in Polymer-Modified Asphalt Mixture. Issue 6 (June 2020) - Park, Bongsuk; Zou, Jian; Roque, Reynaldo; Lopp, George; Wu, Zhengyu
Reclaimed asphalt pavement (RAP), commonly generated from the millings of damaged roads, contains recyclable asphalt and aggregate. Polymer-modified asphalt (PMA) binders have had proven success in mitigating rutting and cracking in asphalt pavements. However, benefits associated with PMA binder may be reduced by aged and more brittle RAP binder. Currently, the maximum usage of RAP in PMA mixture is limited to 10–20% by several Departments of Transportation in the United States. Other than maximum RAP content, no criterion related to RAP characteristics is used to limit RAP usage in PMA mixture. Recent studies showed RAP binder stiffness and RAP aggregate gradation appeared to be important characteristics related to cracking performance of PMA mixture containing RAP. Therefore, this research focused on determining maximum allowable RAP content in PMA mixture for individual RAP sources based on key RAP characteristics identified, that is, RAP stiffness and RAP fineness. Interstitial component direct tension (ICDT) test was conducted to determine fracture energy for interstitial component (i.e., the fine portion of PMA mixture containing RAP), which is known to be correlated well with the fracture energy of the corresponding mixture. Results showed introduction of coarser and less stiff RAP generally resulted in greater fracture energy, which allowed up to 40% RAP usage in PMA mixture. Integration of key RAP characteristics identified and the results of ICDT test provide a systematic approach for determination of maximum RAP content in PMA mixtures. Further research is recommended to evaluate additional RAP sources to verify the proposed approach.